Simplify the following:
((-1^3)/(-3)^(-3))^2
1^3 = 1:
((-1)/(-3)^(-3))^2
(-3)^(-3) = 1/(-1)^3×1/3^3 = (-1)/3^3:
((-1)/((-1)/3^3))^2
3^3 = 3×3^2:
((-1)/(-1/(3×3^2)))^2
3^2 = 9:
((-1)/((-1)/(3×9)))^2
3×9 = 27:
((-1)/((-1)/27))^2
Multiply the numerator of (-1)/((-1)/27) by the reciprocal of the denominator. (-1)/((-1)/27) = (-27)/(-1):
((-27)/(-1))^2
(-27)/(-1) = (-1)/(-1)×27 = 27:
27^2
| 2 | 7
× | 2 | 7
1 | 8 | 9
5 | 4 | 0
7 | 2 | 9:
Answer: 729 = 1/729 thus c: is your Answer
Answer:
25 minutes and 33 seconds
Step-by-step explanation:
please brainiest
Answer:
no
Step-by-step explanation:
6-6=0
1-6=-5
Answer:
n=35
Step-by-step explanation:
Isolate the variable by dividing each side by factors that don't contain the variable
Answer:
See below.
Step-by-step explanation:
This is conveniently done using a 24-hour representation of the given time:
... 2:30 pm = 14:30
Honolulu = 14:30 -10 = 4:30 . . . . 4:30 am
London = 14:30 - 0 = 14:30 . . . . 2:30 pm
Los Angeles = 14:30 -8 = 6:30 . . . . 6:30 am
Paris = 14:30 +1 = 15:30 . . . . 3:30 pm
Tokyo = 14:30 +9 = 23:30 . . . . 11:30 pm
Washington = 14:30 -5 = 9:30 . . . . 9:30 am